Ultraviolet specular reflectance, electronic absorption and the excitation of fluorescence in single crystals of anthracene - Wright, W H (Rhodes University, Faculty of Science, Department of Physics, 1966)
From introduction: The Fluorescence Excitation Spectrum or anthracene is known to vary considerably with the age and condition or the crystal. This thesis represents an attempt to improve the understanding of these variations. To put the problem on a quantitative basis it was found necessary to know both the ultraviolet reflection and absorption spectra. Reports of the reflection spectrum appear to have been confined to the case of polarised incident light. In addition the reflectivity measurements are always reported for a freshly cleaved surface. For these reasons the reflectivity of anthracene for various conditions of the reflecting surface was measured with unpolarised light. These varying reflectivities were used to further knowledge of the chemical processes at the crystal surface, as well as being used directly in the calculation of fluorescence excitation spectra. Reflection spectra with a- and b- crystallographic axis polarisations were also obtained. Since such spectra are reported in the literature it was possible, by comparison, to conclude that the experimental methods used in this thesis yielded valid results. The polarised measurements were used to obtain optical constants for the crystal. In the interests of readability most of the complicated process of converting the reflectivities to optical constants is dealt with in three appendices to the thesis.
Keywords: Anthracene crystals -- Fluorescence; Ultraviolet spectroscopy -- Absorption; Reflectance